Valeria Belvedere Milano 1987 - 1989. - Valeria Belvedere, Milano (Milano : Electa, 1989)
Bartolini, Luciano ; Pizzi Cannella, Nunzio ; Guerzoni, Franco ; Nagasawa ; Cragg, Tony ; Flavin, Dan ; Judd, Donald ; Long, Richard ; Coletta, Pietro ; Fusco, Mario ; Icaro, Paolo ; Quartana, Luca ; Fogliati, Piero ; Mattiacci, Eliseo
Overzicht tentoonstellingen van oktober 1987 tot september 1989
boek